2006
DOI: 10.1002/bjs.5356
|View full text |Cite
|
Sign up to set email alerts
|

Development, implementation and prospective evaluation of guidelines for transfer of severely injured children to specialist centres

Abstract: The introduction of triage guidelines within an effective communication network was associated with changes in the management of severely injured children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A number of studies reported substantial improvement in quality both in inpatient [1,11,14,18,21,32,50,53,57,60,62,68,78] and outpatient settings [13,29,37,40,42,46]. Numerous studies, including six RCTs [4,7,38,51,63,71], failed to show any positive effects on quality associated with practice guidelines [5,10,20,25,26,36].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%
“…A number of studies reported substantial improvement in quality both in inpatient [1,11,14,18,21,32,50,53,57,60,62,68,78] and outpatient settings [13,29,37,40,42,46]. Numerous studies, including six RCTs [4,7,38,51,63,71], failed to show any positive effects on quality associated with practice guidelines [5,10,20,25,26,36].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%